PROSES IMPLEMENTASI KEBIJAKAN REKLAME MENGENAI TATA CARA PEMBERIAN IZIN DAN PENERTIBAN DI KOTA PONTIANAK - Dwi Agus Muharria E.01107111 (FISIP Universitas Tanjungpura, 2012)
AbstractAdvertising is one of the means used by the government publicly or privately to communicate and provideinformation to the public. However, many of the issues concerning the implementation of the billboard interms of hooking up demolition permit is not done properly will give the impression kesemerautan andlaying haphazardly in the billboard. It is caused by a lack of coordination and control among theinstitutions involved in granting permits, set the location of the billboard installation, and low intensity ofsocialization in terms of how the procedure for the organization is good publicity. Advertising-mountedbillboard that had matured during the installation of billboards are usually removed and acted too slowly.This is very important because it will interfere with the beauty of the city, making it harder to put upanother billboard operators and can harm the advertisement revenue. Local authorities should coordinateto regulate billboards, providing data advertisement and problematic due to be addressed by the lawenforcement officers pay more attention to advertising and principal functions and duties of each. Givegood extension to the community aims to facilitate the public to better understand, understanding, open upthe smooth communication and assist in maintaining the attributes of an existing billboard. In addition, thegovernment should also do additional section or sections that specifically deal with the installationprocedure of advertisement. Because if you can not pay more attention to the situation and conditions in thefield can not be well ordered.Keywords: Procedures For Licensing, Licensing Implementation Billboards, Advertising Placement andControl